1997
DOI: 10.1055/s-0038-1655947
|View full text |Cite
|
Sign up to set email alerts
|

A Common Thrombomodulin Amino Acid Dimorphism Is Associated with Myocardial Infarction

Abstract: SummaryEndothelial dysfunction and haemostatic imbalance are believed to be important aetiological factors in the development of acute coronary syndromes. Thrombomodulin (TM) is an integral membrane protein crucial for normal endothelial function and activation of the protein C anticoagulant pathway. We have investigated the importance of a common C/T dimorphism in the TM gene (nucleotide 1418) for development of premature myocardial infarction (MI). The C/T dimorphism predicts an Ala455 to Val replacement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
5
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 16 publications
(22 reference statements)
3
60
5
3
Order By: Relevance
“…Table 2 shows the genotype distribution. Among the 1262 healthy subjects, the frequency of the 1418T allele was 0.175, which is similar to that reported in previous studies (0.180, 19 0.169, 23 and 0.184 27 ) but lower than in other studies (0.261 20 and 0.280 25 ). Given that the control subjects were recruited in 3 different geographical areas of Spain, we analyzed the 1418T allele frequency in the 3 control populations.…”
Section: Thbd C1418c>t Polymorphism and Vte Risksupporting
confidence: 79%
See 1 more Smart Citation
“…Table 2 shows the genotype distribution. Among the 1262 healthy subjects, the frequency of the 1418T allele was 0.175, which is similar to that reported in previous studies (0.180, 19 0.169, 23 and 0.184 27 ) but lower than in other studies (0.261 20 and 0.280 25 ). Given that the control subjects were recruited in 3 different geographical areas of Spain, we analyzed the 1418T allele frequency in the 3 control populations.…”
Section: Thbd C1418c>t Polymorphism and Vte Risksupporting
confidence: 79%
“…However, its association with venous [19][20][21][22][23] and arterial thrombosis [24][25][26] is not consistent. In the present study, we investigated the association of this polymorphism with VTE and plasma TM and activated PC (APC) levels.…”
mentioning
confidence: 99%
“…46 Two polymorphisms have been identified in the thrombomodulin gene that code for Ala455Val and Ala25Thr amino acid substitutions. One report suggested an association between the former and MI, 47 but this has not been confirmed. In the Study of Myocardial Infarctions Leiden (SMILE), the Ala25Thr substitution was found to increase the risk of MI, particularly in smokers (OR, 8.8; 95% CI, 1.8 to 42.2) 48 ; however, there is no biologic evidence that the 25Thr isoform alters protein function.…”
Section: Thrombomodulinmentioning
confidence: 94%
“…In conjunction with its cofactor protein S, activated protein C degrades coagulation cofactors Va and VIIa, thereby attenuating the coagulation cascade (5,6). The importance of the anticoagulant properties of activated protein C is highlighted by the fact that patients with congenital or acquired deficiencies in the activated protein C anticoagulant pathway are prone to venous and arterial thrombosis (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%